Frequency of Prolonged QTc Interval in Patients with Cirrhotic Liver Disease in Medical Unit-4 DHQ Hospital Faisalabad - Rasool, Hina; Muhammad Arslan (Indus Journal of Bioscience Research, 2025)
Background: Cirrhotic liver disease is linked to a number of abnormalities in the cardiovascular system such as prolongation of the corrected QT (QTc) interval, which may predispose patients to life-threatening arrhythmia. QTc prolongation has been recognized as a part of cirrhotic cardiomyopathy increasingly and is believed to get worse with the progression of liver disease. Early identification is necessary to reduce morbidity and mortality. Objective: To calculate the frequency of prolonged QTc interval in patients with cirrhotic liver disease, and to evaluate the association between prolonged QTc and demographic and clinical variables. Methodology: This descriptive cross sectional study was carried out from the Department of Medicine, DHQ Hospital Faisalabad during the period of 6 months. A total of 145 clinically diagnosed cirrhotic patients aged between 18-60 years old were recruited using non-probability consecutive sampling technique. Patients with cardiac diseases, hypertension, chronic renal failure, COPD or pregnancy were excluded. After informed consent, clinical assessment, laboratory tests, ultrasound of abdomen and standard 12-lead ECG were carried out in detail. QTc was calculated by Bazett ka formula. Data were analyzed in SPSS 25. Mean +- SD were reported for quantitative variables while frequencies and percentages were used for qualitative data. Results: The mean age of the participants was 40.53 +- 12.74 years and 54.5% were males. Prolonged QTc interval was found in 21.4% of patients. QTc prolongation was significantly linked to female gender (p = 0.005), upper age groups (p = 0.003), higher Child-Pugh class (p < 0.001) and higher severity of the disease (p < 0.001). Conclusion: QTc prolongation is a common electrophysiologic abnormality in cirrhotic patients and is related to higher liver disease severity. Routine ECG screening is advised because it allows early identification and management of small subgroups of high-risk individuals.